Feeding and overwintering of Antarctic krill across its major habitats: The role of sea ice cover, water depth, and phytoplankton abundance. (9th January 2014) - Schmidt, Katrin; Atkinson, Angus; Pond, David W.; Ireland, Louise C.
Abstract : Antarctic krill ( Euphausia superba ) were sampled in contrasting habitats: a seasonally ice‐covered deep ocean (Lazarev Sea), ice‐free shelves at their northern range (South Georgia) and the Antarctic Peninsula (Bransfield Strait), and shelf and oceanic sites in the Scotia Sea. Across 92 stations, representing a year‐round average, the food volume in krill stomachs comprised 71 ± 29% algae, 17 ± 21% protozoans, and 12 ± 25% metazoans. Fatty acid trophic markers showed that copepods were consistently part of krill diet, not a switch food. In open waters, both diatom and copepod consumption increased with phytoplankton abundance. Under sea ice, ingestion of diatoms became rare, whereas feeding on copepods remained constant. During winter, larvae contained high but variable proportions of diatom markers, whereas in postlarvae the role of copepods increased with krill body length. Overwintering differed according to habitat. Krill from South Georgia had lower lipid stores than those from the Bransfield Strait or Lazarev Sea. Feeding effort was much reduced in Lazarev Sea krill, whereas most individuals from the Bransfield Strait and South Georgia contained phytoplankton and seabed detritus in their stomachs. Their retention of essential body reserves indicates that krill experienced most winter hardship in the Lazarev Sea, followed by South Georgia and then Bransfield Strait. This was reflected in the delayed development from juveniles to adults in the Lazarev Sea. Circumpolar comparisons of length frequencies suggest that krill growth conditions are more favorable in the southwest Atlantic than in the Lazarev Sea or off East Antarctica because of longer phytoplankton bloom periods and rewarding access to benthic food.